Effect of Fuel Subsidy Removal on Tomatoes Production in Garun Mallam Local Government Area, Kano State, Nigeria - Okwoli, Wilson Simon; Dutse, Asma’u I; Adegbe, Ojonoka Veronica (Kashere Journal of Politics and International Relations, 2025)
The study examined the socio-economic impact of the fuel subsidy removal on food scarcity in Nigeria, with a specific focus on tomatoes production in Garun Mallam Local Government Area, Kano. The research aimed to assess how the removal of fuel subsidies has affected tomatoes production, analyze its socio-economic consequences, and identify potential solutions to mitigate the negative effects. The study relied on the Price Pass-Through Theory as its theoretical framework and adopted a survey method, using questionnaires and in-depth interview as the main instrument for data collection. The study found that the fuel subsidy removal significantly increased production and transportation costs for tomatoes farmers. Higher fuel prices led to greater expenses in transporting tomatoes to both local and regional markets, which resulted in reduced supply and fewer deliveries. The study also highlighted a decline in the volume of tomatoes available for sale as farmers faced challenges in meeting market demand, due to the higher costs of production and transportation. This ultimately impacted the profitability and productivity of tomatoes farmers. The study contributes to knowledge by highlighting the interconnectedness of fuel prices, agricultural productivity, and food security in Nigeria. It also provides insights into the challenges faced by farmers in rural areas, particularly in adapting to the economic implications of national policy changes. The study recommends that the Nigerian government provide targeted subsidies for essential agricultural inputs, such as fertilizers, seeds, and irrigation equipment, to help mitigate the rising production costs caused by the fuel subsidy removal among other recommendations.